ROKAT PANDHABAH TRADITION AND THE DIALECTICS OF THE QUR’AN: A STUDY OF THE LIVING QUR’AN IN MADURA - Sahidah, Ahmad; Anisa, Siti (Universitas Nurul Jadid, 2023)
Along with the times, the study of the Qur’an continues to experience developments in the context of the study area, from what was originally only a text study to a socio-cultural study, which made Muslim society the main object of study known as the study of the living Qur’an. One of the living Qur’an phenomena is the rokat pandhabah tradition of the people of Jenangger Village, Batang Batang District, Sumenep Regency. It is a tradition inherited from our ancestors, preserved and maintained until now. In addition, rokat pandhabah manifests the Jenangger people’s endeavour to resist the coming of bad things that will happen. The purpose of this study is to photograph a tradition that is in dialogue with the Qur’an within the framework of the rokat pandhabah tradition in Jenagger Madura. This study uses a qualitative method of phenomenological type, a research flow that produces descriptive data in the form of written or spoken words from the people observed. For the presentation of data based on the results of interviews and literature review (library research). In the end, this research resulted in a conclusion that the rokat pandhabah tradition is categorized as a living Qur’an phenomenon because there are several factors, namely 1) the rokat pandhabah tradition as a form of endeavour for one’s salvation, 2) the rokat pandhabah tradition as a prayer to predecessors who are gone, 3) the rokat pandhabah tradition as a form of charity to relatives and neighbours, and 4) the rokat pandhabah tradition as a medium in cultural propaganda.